Genealogical tracing of founder variants linked to cardiomyopathies in a South African cohort - Houghton, Abbey (Department of Medicine, 2025)
Introduction: Cardiomyopathies are a major cause of heart failure in South Africa, yet their prevalence, causes, and outcomes remain poorly understood. The IMHOTEP registry was established to clinically and genetically characterise affected patients and through this study several common pathogenic variants were identified, suggesting potential founder variants. This study aimed to genealogically trace the origins of these variants in the probands and their families. Methods: Participants were recruited from South African tertiary hospitals, with baseline data recorded at enrolment. Next generation sequencing identified several probands with possible founder variants which prompted haplotype construction and genealogical tracing. Variants were identified in the genes PKP2, LMNA, BAG3 and TTN and three microsatellite markers, spanning the 5', intergenic and 3' regions, were designed for each of the genes of interest in order to perform haplotype analysis. Genealogical data was collected using online resources, genealogy databases, and the voter's roll. Results: Five PKP2 c.1162C>T (p.Arg388Trp), BAG3 c.925C>T (p.Arg309Ter), LMNA c.568C>T (p.Arg190Trp), TTN c.87624C>G (p.Tyr29208Ter), and TTN c.95008C>T (p.Arg31670Ter) possible founder variants were identified in 38 probands (12 probands with the PKP2 variant; 3 probands with BAG3 variant, three probands with LMNA variant and 20 probands with the two TTN variants). PKP2 was traced to Afrikaner families of Dutch/French Huguenot descent from the 1600s. BAG3 was linked to French-Huguenot and Canadian ancestry. LMNA tracing was limited due to the number of families as well as limited Mixed-Ancestry family records. TTN variants had issues with haplotyping and genealogical challenges as well as limited records for Black African and Mixed-Ancestry families. Conclusions: This research significantly advances our understanding of cardiomyopathy genetics in South Africa. The identification of Dutch/French and French-Canadian ancestries associated with the PKP2 and BAG3 variants, respectively, provides valuable insights into the historical origins and population-specific genetic landscape of these cardiomyopathies. This ancestral information not only deepens our understanding of cardiomyopathy in the region but also has important implications for risk assessment and genetic counselling. By identifying common progenitors, we can better target screening efforts and provide more accurate risk assessments for individuals carrying these founder variants